MARSIADAPARI SEBAGAI SOLIDARITAS SOSIAL BATAK DALAM GEREJA DAN MASYARAKAT - Arif Ebenejer Simangunsong; Riris Johanna Siagian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the social and spiritual values of the marsiadapari tradition as a distinctive form of solidarity within the Batak Toba community that remains relevant to the life of the church and modern society. The marsiadapari practice refers to a mutual cooperation system in agricultural work and social activities, founded upon togetherness, love, and collective responsibility. In a theological context, the values of marsiadapari reflect the Christian principles of koinonia (fellowship) and diakonia (service of love). Using a qualitative-descriptive approach, this research analyzes the interaction between Batak local traditions and Christian ethos in building contextual social solidarity. The marsiadapari practice can serve as a model for the church’s social praxis in realizing faith that works through love, while also addressing the challenges of individualism and social inequality in society. The church is called to revitalize the marsiadapari values as part of its social mission so that Christian faith is not only expressed in liturgy but also in concrete acts of solidarity with others. Thus, marsiadapari is not merely a cultural heritage but also a contextual expression of faith that strengthens social cohesion, deepens the spirituality of togetherness, and revives the spirit of loving service within contemporary Batak Christian communities.